Fundamentos del reconocimiento constitucional de los derechos hereditarios del concubino en equiparación al cónyuge - Fustamante Reyna, Juanita Marily (2010)
Raise the issue on which are the main foundations supporting the constitutional recognition of hereditary rights in favor of the concubine own, has imported set as the primary objective the identify, assess and sustain such fundamentals, which are within of social, economic and legal demonstrated in the results of this research, having been obtained from the information used, which has become the theoretical framework this report supports the well after application of the methodology concerned, it became possible identify the aforementioned results, as are cohabiting fulfill the same roles and duties of spouses in the life daily (as a couple and parents) are members united by affection and give rise to a family is made under the scope of the constitutional principle full family protection; them applies the fundamentals of inheritance for the spouse, under the principle of equality and the legal maxim applying A pari; constitutes an objective situation that cohabiting partners are a reality social and economic undeniable and strong presence in Peru and other countries, many of which they are recognizing rights hereditary. Finally, it should be noted that has arrived as a definitive conclusion, that cohabiting couples own their share enjoy constitutional treatment and comparable to legal spouses inheritance matters, as to the condition and position as heirs to the legal consequences arising from this situation